BENEFICIATION OF SAMBIROTO SILICA SAND BY CHEMICAL AND BIOLOGICAL LEACHINGS - Suratman Suratman; Sri Handayani (Puslitbang tekMIRA, 2014)
The commercial value of silica sand significantly affected by the presence and content of iron, aluminium and other metal impurities that can have detrimental effects on the manufactured product. A leaching technology on Sambiroto silica sand had been studied using chemical (HCl and H2SO4) and biological (Aspergillus niger’s metabolite) methods to remove undesired metal impurities and obtain a high purity silica. The rates and extent of chemical leaching and bioleaching were different depending on the leaching agents used and their concen- trations. The results showed that the laboratory experiments improved the silica sand sample to a high grade purity. The major and minor impurities of Fe, Al, Ca, Cr, Ti, Zr and Cu were reduced significantly by acid leaching with HCl and H2SO4 4M at 90°C, 30% pulp density for 4-hours process. The chemical composition of the silica sand improved with the SiO2 content increased from 97.24 to 98.77%, on the other hand, the sum of impurities decreased from 1.148 to 0.237 %. These changes bring the beneficiated product very close to a feedstock of metallurgical grade silicon for advanced materials. Among the tested methods, chemical leaching is the most efficient in terms of both increasing percentage of SiO2 and metal impurities removal compared to biological leaching. Nevertheless, bioleaching process is sufficient to produce silica sand with a desired minimum value of Fe and Al contents for high quality glass industries. Both process characteristics could facilitate their industrial applications.